2022
DOI: 10.1177/17534666221122544
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic importance of the angiotensin II/angiotensin-(1–7) ratio in patients with SARS-CoV-2 infection

Abstract: Background: Information about angiotensin II (Ang II), angiotensin-converting enzyme 2 (ACE2), and Ang-(1–7) levels in patients with COVID-19 is scarce. Objective: To characterize the Ang II–ACE2–Ang-(1–7) axis in patients with SARS-CoV-2 infection to understand its role in pathogenesis and prognosis. Methods: Patients greater than 18 years diagnosed with COVID-19, based on clinical findings and positive RT-PCR test, who required hospitalization and treatment were included. We compared Ang II, aldosterone, Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
1
17
0
1
Order By: Relevance
“…In COVID-19 patients, lower Ang-(1–7) levels influenced the activation of multiple immunological responses and disseminated coagulation [ 54 ]. Furthermore, the COVID-19 patients, who died, had lower serum Ang-(1–7) levels and correspondingly higher Ang II/Ang-(1–7) levels [ 55 ]. Thus, the Ang II/Ang-(1–7) concentrations could be regarded as independent predictors of COVID-19 mortality [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 patients, lower Ang-(1–7) levels influenced the activation of multiple immunological responses and disseminated coagulation [ 54 ]. Furthermore, the COVID-19 patients, who died, had lower serum Ang-(1–7) levels and correspondingly higher Ang II/Ang-(1–7) levels [ 55 ]. Thus, the Ang II/Ang-(1–7) concentrations could be regarded as independent predictors of COVID-19 mortality [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining RAS imbalance in patients with COVID-19 exhibit conflicting results. In one study, it was shown that patients with COVID-19 had elevated levels of Ang II and low levels of Ang 1–7 despite high ACE-2 activity compared to control subjects ( Amezcua-Guerra et al, 2022 ). There was also a significant increase in Ang II/Ang 1–7 ratio that correlated with decreased ACE-2 activity ( Amezcua-Guerra et al, 2022 ).…”
Section: Mechanisms Of Autonomic Dysfunction By Sars-cov-2mentioning
confidence: 99%
“…In one study, it was shown that patients with COVID-19 had elevated levels of Ang II and low levels of Ang 1–7 despite high ACE-2 activity compared to control subjects ( Amezcua-Guerra et al, 2022 ). There was also a significant increase in Ang II/Ang 1–7 ratio that correlated with decreased ACE-2 activity ( Amezcua-Guerra et al, 2022 ). Patients who died had a significantly low Ang II/Ang 1–7 ratio ( Amezcua-Guerra et al, 2022 ).…”
Section: Mechanisms Of Autonomic Dysfunction By Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations